Electric Fields and Inflammation: May the Force be with You - Simon B. Brown; Ian Dransfield (The Scientific World Journal)
Integrins are a family of ubiquitous cell surface receptors comprising heterodimers of β and α chains that are required for cell adhesion and motility. Integrin-dependent adhesion and signaling is associated with major conformational changes in the ectodomain as it shifts from a low-affinity “bent” to a high-affinity “extended” structure. The ability of a cell to regulate dynamically the affinity or activation state of an integrin, and hence its binding to extracellular matrix or cell adhesion molecules, is assumed to be driven by intracellular signaling events transmitted by protein binding to the cytoplasmic tail. The binding of an integrin to its ligand can then transmit signals back into the cell to regulate the formation of a macromolecular focal adhesion complex that effectively anchors the cytoskeleton to the adhesion site. Many proteins have been reported to associate physically and functionally with integrins, leading to altered signaling events. A particularly intriguing molecular association exists between integrins and transmembrane proteins that gate the movement of charge, especially voltage-gated potassium channels, although the significance of this interaction is not understood. Although ample evidence indicates that the engagement of integrins can promote potassium efflux by both excitable and nonexcitable cells, we speculate the converse, that the activation state of integrins is dynamically regulated by changes in a transmembrane potential. In this way, direct-current electric fields generated at a site of tissue injury can promote the galvanotaxis or directed migration of cells involved in tissue repair and inflammation.